Improved pseudopotential lattice Boltzmann model for liquid water transport inside gas diffusion layers. (26th April 2021) - Yang, Jiapei; Fei, Linlin; Zhang, Xiaoqing; Ma, Xiao; Luo, Kai H.; Shuai, Shijin
Abstract: Liquid water transport inside the gas diffusion layers (GDLs) plays a vital role in water management of proton exchange membrane fuel cells (PEMFCs). In this study, an improved pseudopotential multiphase lattice Boltzmann model is firstly developed to realize the actual density and viscosity ratios in porous media. The proposed model is based on a non-orthogonal multiple-relaxation-time (MRT) LB model and a new improved wettability boundary condition. In terms of the relationship between capillary pressure P c and saturation s, the proposed model shows a good agreement with the experimental data. Using the validated model, the effects of capillary pressures and contact angles of mixed wettability on the liquid water invasion process for Toray-090 GDLs with two Polytetrafluoroethylene (PTFE) contents (10 wt% and 20 wt%) are studied. It is found that the liquid water shows capillary fingering behaviors and the liquid water saturation profiles along the through-plane direction of the GDLs become more non-uniform with increasing contact angle of PTFE. Highlights: An improved pseudopotential LB model with the high density ratio in GDL is developed. Pc - s curves of the proposed model results agree well with the experimental data. Effects of the pressure and mixed wettability on the invasion process are studied.